Revealing the Reaction Mechanism of Na-O-2 Batteries using Environmental Transmission Electron Microscopy - Kwak, Won-Jin; Luo, Langli; Jung, Hun-Gi; Wang, Chongmin; Sun, Yang-Kook (AMER CHEMICAL SOC, 2018)
Sodium oxygen (Na-O-2) batteries are being extensively studied because of their higher energy efficiency compared to that of lithium oxygen (Li-O-2) batteries. The critical challenges in the development of Na-O-2 batteries include the elucidation of the reaction mechanism, reaction products, and the structural and chemical evolution of the reaction products and their correlation with battery performance. For the first time, in situ transmission electron microscopy was employed to probe the reaction mechanism and structural evolution of the discharge products in Na-O-2 batteries. The discharge product was featured by the formation of both cubic and conformal NaO2. It was noticed that the impingement of the reaction product (NaO2) led to particle coarsening through coalescence. We investigated the stability of the discharge product and observed that the reaction product NaO2 was stable in the case of the solid electrolyte. The present work provides unprecedented insight into the development of Na-O-2 batteries.
Keywords: HIGH-ENERGY EFFICIENCY; DISCHARGE PRODUCTS; OXYGEN BATTERIES; LITHIUM; NAO2; INSTABILITY; STABILITY; INSIGHTS; CELLS